AN ANALYSIS OF LEARNING DIFFICULTIES IN INDONESIAN LANGUAGE AMONG ELEMENTARY, JUNIOR HIGH, AND SENIOR HIGH SCHOOL STUDENTS - Manurung, Rolan; Sitohang, Tigor; Reynhat Sitanggang Gusar, Martua; Patresia Girsang, Nais; Rohmahaldo Purba, Evin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This study aims to analyze the various difficulties students face in learning the Indonesian language at the elementary (SD), junior high (SMP), and senior high school (SMA) levels using a literature review approach. Data were gathered from more than 15 primary and secondary sources, including academic journals, textbooks, and previous research findings. The study identifies six major dimensions of language learning difficulties: linguistic, pedagogical, psychological, affective, cognitive, and socio-cultural. Each educational level presents unique challenges—ranging from weak basic literacy skills in elementary school, low motivation in junior high, to underdeveloped critical thinking in high school. These findings highlight the need for contextual, communicative, and literacy-based teaching strategies to improve the effectiveness of Indonesian language instruction. This study contributes to the theoretical and practical understanding of language learning challenges in the national education context. The research underscores the importance of tailoring language instruction to address specific challenges at each educational level. Implementing targeted interventions, such as phonics-based approaches for elementary students and critical thinking exercises for high school learners, could significantly enhance language acquisition outcomes. Furthermore, the study's multidimensional framework provides a comprehensive foundation for developing more effective language teaching methodologies in Indonesia's diverse educational landscape.